2015
DOI: 10.1051/0004-6361/201425167
|View full text |Cite
|
Sign up to set email alerts
|

Elemental abundances associated with gamma-ray bursts: nucleosynthesis in outflows

Abstract: Aims. Outflows from accretion disks have been suggested to be suitable sites for producing heavy elements. The objective of this work is to investigate nucleosynthesis in the outflows launched from the inner accretion disks of collapsars that are associated with gamma-ray bursts (GRBs). Methods. By using a collapsar model of advection-dominated accretion and an adiabatic expanding outflow model, we simulated chemical yields inside the outflows associated with GRBs. As a result of the extremely high temperature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 105 publications
(116 reference statements)
1
2
0
Order By: Relevance
“…Several of these models find considerable production of IME and IGE, and in some cases comparable to our findings (e.g. Hu (2015) up to a factor of a few), however, these models and the regimes in these various works are considerably different than those we explore, and are thus not directly comparable.…”
Section: Comparison To Previous Worksupporting
confidence: 78%
“…Several of these models find considerable production of IME and IGE, and in some cases comparable to our findings (e.g. Hu (2015) up to a factor of a few), however, these models and the regimes in these various works are considerably different than those we explore, and are thus not directly comparable.…”
Section: Comparison To Previous Worksupporting
confidence: 78%
“…Surman et al (2011) focused on nucleosynthesis, particularly for the progenitor of 56 Ni in the hot outflows from GRB accretion disks. Metzger et al (2011) suggested that the composition of ultrahigh energy cosmic rays becomes dominated by heavy nuclei at high energies forming GRB jets or outflows (also see e.g., Sigl et al 1995;Horiuchi et al 2012;Hu 2015).…”
Section: Nucleosynthesismentioning
confidence: 99%
“…Statistical analysis of the bolometric properties of SNe shows that the average 56 Ni mass is 0.4 ± 0.2 M ⊙ in an explosion (e.g., Cano et al 2017). Additionally, during the explosive burning of the collapsar, 56 Ni synthesis also occurs in the hyperaccretion disk (e.g., Chakrabarti et al 1987;Surman et al 2008;Liu et al 2013) or the winds/outflows from the accretion disk (e.g., Pruet et al 2004;Kohri et al 2005;Surman & McLaughlin 2005;Surman et al 2006Surman et al , 2011Hu & Peng 2008;Liu et al 2013;Hu 2015;Wu et al 2016). This disk is widely considered the main factory of 56 Ni in these studies.…”
Section: Introductionmentioning
confidence: 99%